2018
DOI: 10.1007/s10567-018-0262-9
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Adolescent Peer Relations in the Social Media Context: Part 2—Application to Peer Group Processes and Future Directions for Research

Abstract: As social media use becomes increasingly widespread among adolescents, research in this area has accumulated rapidly. Researchers have shown a growing interest in the impact of social media on adolescents' peer experiences, including the ways that the social media context shapes a variety of peer relations constructs. This paper represents Part 2 of a two-part theoretical review. In this review, we offer a new model for understanding the transformative role of social media in adolescents' peer experiences, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
280
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(296 citation statements)
references
References 149 publications
(242 reference statements)
11
280
2
3
Order By: Relevance
“…Coping motives refer to using Internet to forget about problems and to cheer oneself up when in bad mood, while conformity motives refer to Internet use to be liked by others and not being excluded (Bischof-Kastner et al, 2014). The fact that traditional victims reported to favor these kind of motives further supports the hypothesis that youth who are target of peer victimization in their offline life may tend to use the Internet to escape from their negative face-to-face experiences and related distress, on the one hand, and to try to fit in, enhance their social status, and feel accepted in a peer group, on the other one (Nesi, Choukas-Bradley, & Prinstein, 2018). It remains unclear whether these victims are actually able to satisfy these specific needs in their online life or, conversely, continue to encounter problems in relationships with peers and, in the most negative cases, begin to suffer also from cyber-victimization becoming dual victims.…”
Section: Discussionsupporting
confidence: 56%
“…Coping motives refer to using Internet to forget about problems and to cheer oneself up when in bad mood, while conformity motives refer to Internet use to be liked by others and not being excluded (Bischof-Kastner et al, 2014). The fact that traditional victims reported to favor these kind of motives further supports the hypothesis that youth who are target of peer victimization in their offline life may tend to use the Internet to escape from their negative face-to-face experiences and related distress, on the one hand, and to try to fit in, enhance their social status, and feel accepted in a peer group, on the other one (Nesi, Choukas-Bradley, & Prinstein, 2018). It remains unclear whether these victims are actually able to satisfy these specific needs in their online life or, conversely, continue to encounter problems in relationships with peers and, in the most negative cases, begin to suffer also from cyber-victimization becoming dual victims.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, both self-perceived social acceptance and physical appearance may be hurt by quantifiable indices of approval that are rampant on SNSs. For example, a filtered, appearance-enhancing post depicting a positive social event that receives many "likes" may be especially likely to evoke social comparisons and consequently hurt self-perceived social acceptance and/or physical appearance (e.g., Nesi, Choukas-Bradley, & Prinstein, 2018). To our knowledge, only one study has examined the links between these self-perceptions and SNS social comparisons, which found that Facebook upward social comparisons is associated with poorer self-perceived physical appearance and social acceptance (de Vries & Kühne, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, questions arise as to whether online social competence may be transferred to offline social competence, or whether different contexts (i.e., online and offline) may be associated with differences in patterns of social competence. 51 In this regard, the RECS is the first tool to create a bridge between the overarching constructs of offline and online social competence, as well as to quantify the relationship between offline and online social skills. As young people keep being more and more connected, 52 this bridge may allow future studies to investigate the importance of social competence in online contexts.…”
Section: Resultsmentioning
confidence: 99%